2000
DOI: 10.1186/1297-9686-32-3-321
|View full text |Cite
|
Sign up to set email alerts
|

A high-density linkage map of the RN region in pigs

Abstract: The porcine RN locus affects muscle glycogen content and meat quality. We previously mapped the RN locus to chromosome 15. This study describes the identification of polymorphisms for four class I and four class II markers located in the RN region. Resource families were genotyped with F-SSCP markers (fluorescent single strand conformation polymorphism) and microsatellite markers. Subsequent multipoint linkage analysis revealed the order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The IGFBP-5 gene has been mapped on SSC15, and multipoint linkage analysis has revealed the order FN1-IGFBP-5-S1000-S1001-LR8RB-VIL1-RN-Sw936-Sw906 (Looft et al 2000). Together with the results of Rohrer et al (1997), we found that porcine IGFBP-5 is located between 78 and 85 cm (Wang 2006).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The IGFBP-5 gene has been mapped on SSC15, and multipoint linkage analysis has revealed the order FN1-IGFBP-5-S1000-S1001-LR8RB-VIL1-RN-Sw936-Sw906 (Looft et al 2000). Together with the results of Rohrer et al (1997), we found that porcine IGFBP-5 is located between 78 and 85 cm (Wang 2006).…”
Section: Discussionsupporting
confidence: 60%
“…The IGFBP-5 gene was mapped on porcine chromosome 15 (Looft et al 2000). The mRNA for this gene is 966 bp, and the deduced amino acid sequence consists of 252 amino acids and a putative 19 amino acid signal (White et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To date, porcine IGFBP-1 (Inage-Miyake et al 2005), -3 (Lahbib et al 1996), -4 (Wang et al 2005, and -5 (Looft et al 2000) have been mapped on the porcine chromosome but not IGFBP-2. Also, no studies have been done on the association between the polymorphism and the production performance of this gene.…”
Section: Introductionmentioning
confidence: 97%